Treatment with dabigatran or warfarin in patients with venous thromboembolism and cancer - Schulman, Sam; Feuring, Martin (Thrombosis and haemostasis, 2017)
The efficacy and safety of dabigatran for treatment of venous thromboembolism (VTE) were demonstrated in two trials. It is unclear if the results pertain to patients with cancer and VTE. Data from two randomised trials comparing dabigatran and warfarin for acute VTE were pooled. Primary efficacy outcome was symptomatic recurrent VTE and related death from randomisation to the end of the treatment period. Safety outcomes were major, major and clinically relevant non-major, and any bleeding during the oral-only treatment period. Patients with active cancer (=within 5 years) at baseline or diagnosed during the study were analysed. Compared with 4,772 patients without cancer, recurrent VTE occurred more frequently in 335 patients with cancer at any time (hazard ratio [HR] 3.3; 95 % confidence interval [CI], 2.1-5.3) and more often in 114 with cancer diagnosed during the study compared to 221 with cancer at baseline (HR 2.6; 95 % CI, 1.1-6.2). There was no significant difference in efficacy between dabigatran and warfarin for cancer at baseline (HR 0.75; 95 % CI, 0.20-2.8) or diagnosed during the study (HR 0.63; 95 % CI, 0.20-2.0). Major bleeding (HR 4.1; 95 % CI, 2.2-7.5) and any bleeding (HR 1.5; 95 % CI, 1.2-2.0) were more frequent in patients with cancer than without, but with similar incidence in cancer with dabigatran or warfarin. In conclusion, in cancer patients, dabigatran provided similar clinical benefit as warfarin. VTE recurrence or bleeding were similar in patients on dabigatran or warfarin. The efficacy of dabigatran has not been assessed in comparison with low-molecular-weight heparin.